A Role of Socioeconomic Status in Cognitive Impairment Among Older Adults in Macau: A Decomposition Approach - Zhang, Zhuo; Zhao, Yonghua; Bian, Ying (Frontiers in Aging Neuroscience, 2022)
Background To explore the prevalence and inequality of cognitive impairment among older adults in Macau and the contributions of influencing factors to inequality in cognitive impairment. Methods The Montreal Cognitive Assessment (MoCA) was used to measure the prevalence of cognitive impairment. Socioeconomic status scores were used to describe economic level of the subjects. The concentration index was applied to measure the inequality of cognitive impairment associated with socioeconomic status (SES) and decomposed into its influencing factors. Results The prevalence of cognitive impairment was 44.35% in Macau. The concentration index of cognitive impairment among the elderly was −0.165 (95% CI: −0.232 to −0.098), indicating that the prevalence of cognitive impairment was concentrated in households with poor SES. Older age, poor SES, long or short sleep duration, other marital status, poor appetite, no tea/coffee drinking, no religious belief, and depression contributed positively to the inequality of cognitive impairment. Among these factors, SES made the largest contribution to inequality, accounting for 76.74%. Conclusion In Macau, the prevalence of cognitive impairment among people aged 65 years and older is concentrated among those who are in poor economic conditions. Reducing the gap between the rich and the poor at the source, increasing educational level of low SES population and improving their access to healthcare services will help to improve the inequity of cognitive impairment.